Conviviality, disability and design in the city. Issue 5 (September 2018) - Bates, Charlotte
Weaving together observations and insights from ethnographic research gathered over two years, this article considers how design and everyday life intertwine to create convivial places, but also pauses to take in the moments when tensions rise and conviviality fails. To illustrate, the article takes as an example the redevelopment of a small urban square in London, designed by landscape architects Gustafson Porter and completed in 2011. Gustafson Porter's practice is deeply informed by inclusive design, and they strive to design barrier-free environments that 'promote choice, flexibility of use and enable everyone to participate equally'. Taking in both the material design of the square and the social encounters that happen there, the article considers how inclusion and exclusion operate in a public space like General Gordon Square, and reflects on the challenges of making and maintaining conviviality. It suggests that inclusive design might be imagined as a vision of convivial culture in which we live together with difference.